REPORT FOR OCTOBER, 1991 (Tufts Archival Research Center, 2007)
Marginalia; Letter from Frank Ortiz, Labor Management Committee consultant, to Susan Stuntz reporting the different labor unions across the country to whom Ortiz has made presentations on fair taxes and indoor air quality in October 1991.